Bibliografia zawartości Czasopisma Prawno-Historycznego za lata 1948—1967 - Olszewska, Maria; Olszewski, Henryk (Czasopismo Prawno-Historyczne, 1968)
Bibliografia zawartości Czasopisma Prawno-Historycznego za lata 1948—1967